SAT0405 CLINICAL AND PSYCHOLOGICAL PREDICTORS OF GASTROINTESTINAL INTOLERANCE TO METHOTREXATE IN PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Natalello, G.; De Lorenzis, E.; Tanti, G.; Rubortone, P.; Magurano, M. R.; Peluso, G.; Gremese, E.
Abstract : Background: Methotrexate (MTX) is a first-line treatment for psoriatic arthritis (PsA). Gastrointestinal intolerance (GI) to the drug is a common adverse event that limits its use and can be mediated by autonomic dysfunction or classical conditioning phenomena to repeated drug exposure. Anxiety and depression could promote these processes. Objectives: To assess the prevalence of GI to MTX and its association with anxiety and depression in PsA patients. Methods: One hundred unselected PsA patients in stable MTX treatment were characterized by disease characteristics, adherence to treatment by Morisky Medication Adherence Scale (MMAS-8) and comorbidity by Rheumatic Disease Comorbidity Index (RDCI). Depressive and anxious symptoms were assessed by Hospital Anxiety and Depression Scale (HADS). The presence and the severity of nausea, vomiting, abdominal pain and diarrhoea after administration (associative symptoms) and just before or even at the thought of taking MTX (anticipatory symptoms) were recorded. Results: Patients had a mean age of 56.9±12.0 years and a disease duration of 9.5 years (0.1-58.0 years). They were male, smokers and overweight in 40.0%, 20.0% and 65.0% of cases, respectively. The prevalence of both significant anxious and depressive symptoms was 42.0%. DAPSA showed remission, low disease activity (LDA), moderate disease activity (MDA) and high disease activity (HDA) in 24.0%, 41.0%, 32.0% and 3.0% of patients, respectively. MTX was taken orally by 15.0% of patients and associated with another conventional or biological DMARD in 14.0% and 35.0% of cases, respectively. Symptoms of GI to MTX were complained by 69.3% of patients. Specifically, the prevalence of nausea, diarrhea, vomiting and abdominal pain was 59.0%, 23.0%, 21.0% and 30.0% with associative pattern and 43.0%, 12.0%, 10.0% and 16.0% with anticipatory pattern, respectively. Patients with anxious symptoms experienced more frequently moderate to severe associative nausea (71.4% vs 50.0%, p=0.032) and abdominal pain (42.9% vs 20.7%, p=0.017), and anticipatory nausea (42.9% vs 19.0%, p=0.009), vomiting (14.3% vs 6.9%, p=0.046), and abdominal pain (26.2% vs 8.6%, p=0.018) than non-anxious patients. Patients with depressive symptoms more commonly had associative diarrhea (33.0% vs 15.5%, p=0.037), with no difference in the prevalence of anticipatory symptoms. The presence of associative and anticipatory nausea was associated with higher anxiety scores (p=0.006 and p=0.02 respectively) without differences in the depression score. Associative nausea characterized younger patients (p=0.001), female (p=0.02), with lower BMI (p=0.02) and treated with higher MTX doses (p=0.05). Anticipatory nausea was associated with a lower age (p=0.02), a lower BMI (p=0.005), a longer disease duration (p=0.028), a lower DAPSA (p=0.02), an higher MTX doses (p=0.02) and a lower comorbidity burden (p=0.03). The anticipatory and associative nausea determined lower compliance according to MMAS-8 (p=0.007 and p=0.001, respectively). An anxious profile characterized patients with moderate to severe associative nausea also in the logistic regression model corrected for age (≥65 years), gender, BMI (≥25 kg/m2) and MTX dose (≥0.2mg/kg/week) (OR 3.0, IC 1.1-8.4, p=0.036), and patients with anticipatory nausea also in the model corrected for age (≥65 years), gender, BMI (≥25 kg/m2) and MTX dose (≥0.2mg/kg/week) and disease duration (≥6 years) (OR 3.0, IC 1.1-8.0, p=0.027). Conclusion: Up to two-thirds of patients with PsA who have been treated with MTX experienced symptoms of GI, leading to reduced therapeutic adherence. Associative and anticipatory symptoms characterize patients with a specific clinical and psychological profile. Disclosure of Interests: Gerlando Natalello: None declared, Enrico De Lorenzis: None declared, Giacomo Tanti: None declared, Pietro Rubortone: None declared, Maria Rosaria Magurano: None declared, Giusy Peluso: None declared, Elisa Gremese Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer